Old Brick : Charles Chauncy of Boston, 1705-1787 - Griffin, Edward M. (Book collections on Project MUSE., 1980)
Charles Chauncy was a powerful and influential figure in his own time, but in historical accounts he has always been overshadowed by his contemporaries Benjamin Franklin and Jonathan Edwards. When he is remembered today, it is usually as Edwardss chief a.